Cerebral vasculopathy in childhood neurofibromatosis type 2: cause for concern?. (21st May 2018) - Lascelles, Karine; Afridi, Shazia; Siddiqui, Ata; Hemingway, Cheryl; Ferner, Rosalie; Ganesan, Vijeya
Abstract : Unlike adult neurofibromatosis type 2 (NF2), which presents with symptoms related to bilateral vestibular schwannomas, children with NF2 most frequently present with ocular, dermatological, and neurological symptoms. Arteriopathy, a well‐established feature in neurofibromatosis type 1, is not a widely recognized feature of NF2. Here we report three children with NF2 with cerebral arteriopathy and/or arterial ischaemic stroke. Bevacizumab, a vascular endothethial growth factor inhibitor, is an established treatment for rapidly growing vestibular schwannomas; however, it carries a risk of both ischaemic and haemorrhagic stroke. Thus, the role of screening and risk to benefit ratio of bevacizumab in NF2 merit further consideration. What this paper adds: Children with neurofibromatosis type 2 (NF2) may be at increased risk of cerebral vasculopathy and arterial ischaemic stroke. Targeted magnetic resonance angiography should be performed in children with NF2 who are being considered for bevacizumab therapy. What this paper adds: Children with neurofibromatosis type 2 (NF2) may be at increased risk of cerebral vasculopathy and arterial ischaemic stroke. Targeted magnetic resonance angiography should be performed in children with NF2 who are being considered for bevacizumab therapy. This article's abstract has been translated into Spanish and Portuguese. Follow the links from theabstract to view the translations. This article is commented on by Kirkham et al. on pages1199–1200 of this issue.